El derecho al trabajo y a la salud frente al teletrabajo - Morales Torres, María (2022)
This work tries to describe the process of regulation of telework-remote work. It is a qualitative work whose applied method is hermeneutic. Observation through a documentary record was used as a technique. It has been found in the INEI that there is a minimum (5%) who suffer from physical or mental disability or limitation; the highest percentage (21%) are able to work and many are unemployed. In conclusion, there is a presence of disabled people whose activities can be carried out virtually and in this pandemic it would have been appropriate to take advantage of the implementation of the regulations that had already been given. Therefore, the need to regulate work other than face-to-face work remains latent so that all those who cannot do pre-specialization feel included in their right to decent work.